Essential oil of Portenschlagiella ramosissima from Croatia, a rich source of myristicin - Maleš, Željan (Array, 2009)
Summary: Isolation of the essential oil from the ripe fruits of Portenschlagiella ramosissima (Apiaceae) by hydrodistillation yielded 1.2 % (vol./w). By GC-FID and GC-MS analyses on fused silica capillaries with polar and non-polar stationary phases, respectively, 19 compounds representing 98.0 % of the total peak area could be identified. Major constituents were γ-terpinene (41.0 %) followed by myristicin (25.3 %, 257.2 ± 2.70 mg per gram of oil) and p-cymene (14.5 %). As a conclusion, in the sample of P. ramosissima collected in Middle Dalmatia a high content of myristicin could be detected which is in contradiction to previous investigations by Harborne et al